ANALISIS KEBERHASILAN SISTEM E-RETAILER PADA KOMUNITAS DI KOTA BATAM (STUDI KASUS PADA MATAHARI.COM) - Kelven Liong; Dody Firmansyah (JURNAL ILMIAH BETRIK, 2023)
The purpose of this research is to find out whether companies like Matahari.com (old company) are able to compete against other e-commerce start-ups using the Mixed Method approach. This research was conducted with the number of respondents as many as 381 questionnaire respondents and 29 interview respondents. The technique used for sampling is the Cluster technique, disproportionate, random sampling. The hypothesis testing used is the structural model (sem). The results showed that quantitatively the information quality factor, service quality significantly affected the intention to use and user satisfaction, then the system quality factor did not have a significant effect on the intention to use and user satisfaction, while qualitatively the system quality factor significantly affected user satisfaction. but did not significantly influence the intention to use, then the quality of information and service quality did not have a significant effect on the intention to use and user satisfaction.